Assessment of mood in aphasia following stroke: validation of the Dynamic Visual Analogue Mood Scales (D-VAMS) - Barrows, Paul David; Thomas, Shirley A. (SAGE Publications Ltd, 2017)
OBJECTIVES: To validate a non-verbal self-report measure of mood - the Dynamic Visual Analogue Mood Scales (D-VAMS) - against the Hospital Anxiety and Depression Scale (HADS) and assess its suitability as an outcome measure or screening measure for depressed mood following stroke. DESIGN: Cross-sectional observational cohort study. PARTICIPANTS: Forty-six stroke survivors (24% with aphasia) recruited from online, from stroke clubs and via an NHS rehabilitation service. METHODS: A set of seven bipolar scales was developed enabling users to report mood by modifying facial expression images using a slider. Participants completed a tablet/computer task, reporting their mood on these scales mixed randomly with versions which used only words. The HADS was then completed, followed by a repeat run of the two versions in a different, random sequence. RESULTS: Exploratory factor analysis identified one factor consistent with pleasantness of mood accounting for 80% of the variance. Internal consistency of D-VAMS was high ( α = 0.95), and there was a high correlation between face-only D-VAMS scores and HADS total scores ( r = -0.80, P < 0.001), as well as HADS-D/HADS-A subscale scores ( r = -0.73, P < 0.001; r = -0.71, P < 0.001). D-VAMS showed good sensitivity and specificity against HADS, with means of 85%/77% (sensitivity/specificity) against the HADS-D and 80%/77% against the HADS-A across nine cut-offs. CONCLUSION: D-VAMS is a valid and reliable measure likely suitable for assessment of depressed mood in aphasia following stroke. Though D-VAMS performed well as a screening measure in this study sample, further study is needed in the acute stage post-stroke.